2010
DOI: 10.1159/000316136
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Receptors in Vocal Fold Tissue: A Theory about the Influence of Sex Hormones in the Larynx

Abstract: Objective: The larynx is considered a secondary sexual organ. To demonstrate that sex hormones can directly influence laryngeal function, specific receptors in the vocal cord must be identified. Materials and Methods: We searched for estrogen, progesterone and androgen receptors, using an immunohistochemical method, in normal human vocal cords (from 3 cadavers) and in samples of healthy vocal cords and of laryngeal carcinomas from 15 live subjects. Breast and prostate carcinoma were used as controls. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
(46 reference statements)
1
21
0
Order By: Relevance
“…As it has been mentioned before, girls suffering from AN present with a characteristic clinical picture of endocrine dysfunction, such as amenorrhoea, abnormal temperature regulation, abnormal levels of the growth hormone, thyroid stimulating hormone (TSH) or corticotropin-releasing hormone (CHR) [5,6,12,15]. Still, it is known that the voice is particularly sensitive to hormonal changes [7,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As it has been mentioned before, girls suffering from AN present with a characteristic clinical picture of endocrine dysfunction, such as amenorrhoea, abnormal temperature regulation, abnormal levels of the growth hormone, thyroid stimulating hormone (TSH) or corticotropin-releasing hormone (CHR) [5,6,12,15]. Still, it is known that the voice is particularly sensitive to hormonal changes [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of immunohistochemical studies clearly demonstrate that there are hormone receptors on the vocal folds [26][27][28]. However, some papers prove just the opposite [29]. Therefore, other theories explaining the undisputed influence of hormone on voice quality are also considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brunings et al (16) found estrogen and progesterone receptors in the biopsy specimens of the benign vocal fold lesions to be expressed in conjunction with edema. On the other hand, Nacci et al (17) showed that sex hormone receptors were absent in the vocal cords and concluded that the different expression of some growth factors in the laryngeal tissue influenced by hormonal variations might result in vocal changes.…”
Section: Discussionmentioning
confidence: 99%